A GHG reduction obligation for sustainable aviation fuels (SAF) in the EU and in Germany. (May 2021) - Bullerdiek, Nils; Neuling, Ulf; Kaltschmitt, Martin
Abstract: Despite various legal drivers already in place, a large-scale use of sustainable aviation fuels (SAF) is still missing. Thus, bringing SAF for GHG reduction reasons into the day-to-day business more effective market injection mechanisms are needed. In this context, direct and indirect effects of a greenhouse gas (GHG) reduction obligation in the EU and in Germany are analysed, considering an obligation level of 2% in 2023 increasing stepwise to 10% by 2030 following the goals derived from transport-related RED II targets. For such GHG reduction obligations referred to the entire EU 27 and the entire German aviation fuel uplifts, obligation induced SAF demands possibly exceed future SAF production quantities by a factor of about two without effective capacity expansion exceeding the published expansion plans. The considered SAF options lead to an aviation fuel price increases of 5–45% referring to a conventional aviation fuel price of 550 €/t. Aviation related EU ETS and German aviation tax revenues are mostly insufficient to significantly cover obligation-induced SAF costs or additional fuel costs. Fostering a broad spectrum of SAF technologies will thus require obligation related sub-mechanisms, due to (significantly) different SAF compliance costs. Thereby, sub-mandates represent the most effective approach. In terms of obligation avoidance measures, tankering – in contrast to three re-routing options considered – is likely to be economically feasible for airlines and requires appropriate countermeasures. Highlights: Analysis of SAF GHG reduction obligation in the EU/Germany for eleven SAF options with various GHG emissions and economics. Obligation related SAF demands may exceed SAF production capacities until 2030 by a factor of two without further measures. EU ETS/German aviation tax revenues permit only limited SAF financing. Tankering is likely to be economically efficient to avoid an obligation, in contrast to different re-routing alternatives. A broad SAF development must be promoted by obligation sub-mechanism, due to distinct economics of different SAF options.